Efektivitas Program Pemberdayaan Usaha Garam Rakyat di Desa Losarang, Indramayu - Santoso Budi Widiarto; Musa Hubeis; Komar Sumantadinata (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2013)
An ironic thing that Indonesia as maritime country have insufficiency salt problem. Salt is strategic commodities that can be easily produced by evaporation of sea water and policy salts have been issued since the Dutch colonial era. In 2011 the Government of Indonesia make toward self sufficiency salt policy. This research was aimed to analyze the implementation efectivity of Salt Business Empowerment Program (Pemberdayaan Usaha Garam Rakyat or PUGAR). The research design used purposive and snowball sampling to select 70 respondents in Losarang Village at Indramayu. The data were analyzed by using Quantitative Analysis, Qualitative Analysis, SWOT and MAHP. The result showed PUGAR in Losarang, Indramayu implemented with effectiveness. This is indicated by salt production target achieved and increasing the salt farmer welfare. Implementation PUGAR make salt productivity in Losarang 90,43 ton/ha, increasing salt farmer income, empower 17 the People's Business Group Salt (Kelompok Usaha Garam Rakyat or KUGAR) with the amount of 170 salt farmers, give technological innovation and quality salt production and give job for 778 peoples as salt farmers, farm workers and transport workers. Obtained result IFE of salt bussiness is 2,608 and EFE is 2,673. Moreover the research calculate salt business feasibility that known from B/C ratio > 1, business profit margin, appropriate salt area owned by farmers, business gap analysis of salt and break even analysis. Break even analysis to determine the selling price of the large volume of salt and salt production business people to reach the point of no profit and no loss (break even). Key words: Empowerment, Farmers, Government, PUGAR, Salt, Workers